Evolving role of diet in the pathogenesis and treatment of inflammatory bowel diseases. Issue 9 (18th May 2018) - Levine, Arie; Sigall Boneh, Rotem; Wine, Eytan
Abstract : Recent advances in basic and clinical science over the last 3 years have dramatically altered our appreciation of the role of diet in inflammatory bowel diseases (IBD). The marked increase in incidence of these diseases along with the important role of non-genetic susceptibility among patients with IBD has highlighted that these diseases have a strong environmental component. Progress in the field of microbiome and IBD has demonstrated that microbiome appears to play an important role in pathogenesis, and that diet may in turn impact the composition and functionality of the microbiome. Uncontrolled clinical studies have demonstrated that various dietary therapies such as exclusive enteral nutrition and newly developed exclusion diets might be potent tools for induction of remission at disease onset, for patients failing biologic therapy, as a treatment for disease complications and in reducing the need for surgery. We review these advances from bench to bedside, along with the need for better clinical trials to support these interventions.